TUDUHAN PALSU MAHKAMAH AGAMA ATAS PENGADILAN YESUS MENURUT MATIUS 26:57-68 DAN RELEVANSINYA TERHADAP MARAKNYA INFORMASI PALSU DALAM DUNIA DIGITAL - Yulius Defri Sudi; Gregorius Tri Wardoyo (Bahasa Indonesia, 2026)
Matthew 26:57–68 presents one of the darkest moments in the story of Jesus' suffering, namely when He was brought before the Sanhedrin and falsely accused by false witnesses. This event reflects the tension between divine truth and human falsehood rooted in self-interest, envy, and manipulation of power. The false accusations directed at Jesus not only reflect the practices of religious injustice at that time, but also reveal the universal reality of human tendencies to distort facts for certain interests. In the context of the modern world, this phenomenon finds its relevance again in the form of the spread of false information or hoaxes in the digital world. Hoaxes circulating on social media often arise from similar motives, namely the drive for power, group interests, and the desire to shape public opinion through lies. Using an exegetical approach to the text of Matthew 26:57-68 and contextual reflection, this article attempts to explore the theological meaning of the false accusations against Jesus, then draw ethical and pastoral implications for the lives of Christians amid the current flood of false information. The results of this study show that the truth of Christ is the moral foundation that guides believers to be critical, honest, and responsible in facing the era of digital disinformation.